PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMP NEGERI 5 LEDO - Toni, Toni; Aunurrahman, Aunurrahman; Halida, Halida (Academy of Education Journal, 2023)
This research aims to determine the influence of the principal's leadership on teacher performance at SMP Negeri 5 Ledo. This research method is quantitative with a descriptive approach, with questionnaires supported by document studies and interviews to obtain optimal results. The population in this study were teachers at SMP Negeri 5 Ledo, the sample taken was 20 teachers, namely all teachers at SMP Negeri 5 Ledo. The results of the research show that there is an influence between the principal's leadership on teacher performance at SMP Negeri 5 Ledo. Judging from the results of the Persial test (T-Test), the Tcount value is 3.581 and the Ttable value is 2.042 with a significance value of 0.002. With the test criteria T count > T table and if significance < 0.05 then H0 is rejected so that there is a significant influence between the principal's leadership on teacher performance at SMP Negeri 5 Ledo. Then the coefficient of determination shows that the R square value is 0.416, namely the influence of the principal's leadership on teacher performance at SMP Negeri 5 Ledo is 25.2%. This means that the influence of the principal's leadership on teacher performance is in the low category out of a total of 100%. However, it can be suggested that school principals should have more control over teachers in making lesson plans and provide supervision over teachers so that their performance improves.